2008
DOI: 10.1038/emboj.2008.263
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the transcriptional regulator LmrR and its mechanism of multidrug recognition

Abstract: LmrR is a PadR-related transcriptional repressor that regulates the production of LmrCD, a major multidrug ABC transporter in Lactococcus lactis. Transcriptional regulation is presumed to follow a drug-sensitive induction mechanism involving the direct binding of transporter ligands to LmrR. Here, we present crystal structures of LmrR in an apo state and in two drug-bound states complexed with Hoechst 33342 and daunomycin. LmrR shows a common topology containing a typical b-winged helix-turn-helix domain with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

10
199
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(210 citation statements)
references
References 38 publications
10
199
1
Order By: Relevance
“…Crystals diffracting to sufficiently high resolution could be obtained only for an LmrR that had the K55 and K59 residues reintroduced. The overall conformation of LmrR is similar to that observed in previously published drug‐bound complexes 28. Electron density in between the indole rings of the central W96/W96′ pair is attributed to the presence of the bound heme.…”
supporting
confidence: 82%
See 1 more Smart Citation
“…Crystals diffracting to sufficiently high resolution could be obtained only for an LmrR that had the K55 and K59 residues reintroduced. The overall conformation of LmrR is similar to that observed in previously published drug‐bound complexes 28. Electron density in between the indole rings of the central W96/W96′ pair is attributed to the presence of the bound heme.…”
supporting
confidence: 82%
“…LmrR is a homodimeric protein with a unique and highly dynamic structure that is key to its biological function 28, 29. It presents an unusually large hydrophobic and promiscuous binding pocket at the dimer interface, which has proven to be very suitable for the creation of a novel active site through anchoring of a catalytically active Cu II complex inside.…”
mentioning
confidence: 99%
“…Such binding pockets have been described structurally for at least three multidrug binding transcription regulators including QacR, TtgR, and LmrR. 26,46,47 To this end, it is interesting that all of the analyzed MDR mutations in MexR show extended ANS binding to a hydrophobic surface in the native protein.…”
Section: Discussionmentioning
confidence: 99%
“…None of these characterized regulators belong to the actinomycetes group nor are they involved in antibiotic biosynthesis. This family of proteins typically possesses a conserved N-terminal winged helix-turn-helix DNA-binding domain and a variable C-terminal helical domain involved in dimerization (Arita et al, 2007;De Silva et al, 2005;Fibriansah et al, 2012;Madoori et al, 2009). In LmrR, a flat-shaped hydrophobic pore at the dimer centre serves as a multidrug-binding site, existing in an allosteric coupling between the multidrug-and DNA-binding sites, which is proposed to be involved in the induction mechanism (Madoori et al, 2009 of mithramycin.…”
Section: Discussionmentioning
confidence: 99%
“…This family of proteins typically possesses a conserved N-terminal winged helix-turn-helix DNA-binding domain and a variable C-terminal helical domain involved in dimerization (Arita et al, 2007;De Silva et al, 2005;Fibriansah et al, 2012;Madoori et al, 2009). In LmrR, a flat-shaped hydrophobic pore at the dimer centre serves as a multidrug-binding site, existing in an allosteric coupling between the multidrug-and DNA-binding sites, which is proposed to be involved in the induction mechanism (Madoori et al, 2009 of mithramycin. In accordance with this, transcription analysis of mtrY and resistance genes comparing the mtrYminus mutant with the WT strain showed that all these genes were expressed at a higher level in the former than in the latter.…”
Section: Discussionmentioning
confidence: 99%